(untitled) (Journal of Economic Research & Business Administration, 2019)
Increased globalization has led to the widespread application of project management systems in many areas of business operations. This article is intended to examine the theoretical and methodological approaches to project management in ensuring the competitiveness of the national economy as it pertains to the implementation of its government programs and projects. Through the scientific analysis of current-day publications on project management in the public sector, the authors substantiate the need for its introduction into Kazakhstan’s practice, which will increase the competitiveness of economic activity. The theoretical and methodological substantiation is based on the utilization of the magic triangle of project management: “quality – time – budget”, which makes it possible to develop algorithms for the performance of the main functions of project management by government agencies. The article emphasizes the need to use the international experience in the practical implementation of project management of public authorities in the execution of government programs and projects in the context of global instability, accompanied by various risks, crisis situations, limited resources, and many other effects. In the national science, there is yet a lot to be done on a thorough analysis of a project management system implementation in government agencies on the path of Kazakhstan’s entry into the top 30 most competitive countries in the world. In this regard, this article discusses issues arising in the implementation of the project management system in the government bodies of the Republic of Kazakhstan and ways to address them.